Comparisons on the nutritive values of local and introduced forages and feed mixture for ruminant feed in central dry zone of Myanmar - Moe Thidar Htun, Khin San Mu, Soe Min Thein, Min Aung, Lwin Naing Oo; Hanks, Jenny E.; Stur, Werner W.; Poppi, Dennis P.; Aung, Aung (Journal of Scientific Agriculture, 2017)
This study aimed to compare nutritive values of local (Sorghum) and introduced (Mombasa) forages and their feed mixtures for ruminant feed in central dry zone of Myanmar. Sorghum based feed mixtures (FeedMix-1, 2 and 3) were the commonly used feed mixtures for cattle in dry zone of Myanmar and other feed mixtures (FeedMix-4, 5 and 6) were based on Mombasa. The lower CP and higher fibre contents (P<0.05) were observed in sorghum and its feed mixtures. The highest gas volumes (P<0.05) were observed in the FeedMix-4 and 6, and then the lowest gas volume (P<0.05) was observed in FeedMix-3. The gas production from quickly soluble fraction (a) of sorghum was significantly higher (P<0.05) than that of Mombasa, inversely the gas production from insoluble fraction (b) of sorghum was significantly lower (P<0.05) than that of Mombasa. Moreover, potential gas production (a+b), ME, OMD and SCFA of sorghum were also significantly lower (P<0.05) than those of Mombasa. The value of “a” was lowest (P<0.05) in FeedMix-1, whereas the highest value was found in FeedMix-6. The lowest values (P<0.05) of “b”, “a+b”, ME, OMD and SCFA were observed in FeedMix-3 and the highest values (P<0.05) of those parameters were found in FeedMix-4. Thus, the higher nutritive values observed in the introduced forage, Mombasa and its feed mixtures were indicating that Mombasa should be used instead of sorghum for the feed of cattle in dry zone of Myanmar.